The analysis of the values of squat jump in gymnastics - Lavbic, J.; Pusnik, V.; Samardzija Pavletic, M. (International Scientific Congress Slovenian Gymnastics Federation, 2019)
The aim and purpose of our article was to analyse the parameters of the squat jumps in men`s sports gymnastics (MSG), women`s sports gymnastics (WSG) and rhythmic (RG) gymnastics, and to familiarize sports coaches on the role of sports diagnostics to improve fitness for the purpose of preventing injuries and achieving top results. The study included 77 subjects: 20 WSG competitors, 29 MSG competitors, and 28 RG competitors. In accordance with the aims of the study, we initially determined the jump height in individual disciplines and found that men on average achieved higher jumps (med=0.30) compared to women (WSG, med=0.24; RG, med=0.20). Later, we studied the following parameters that influence the height of the jump and used the time of concentric contraction (Push_Off) and the time to reach the maximum force on the substrate (T_Fmax). We found out that both accompanying parameters are considerably too long in comparison with the studies carried out in this field. The Push_Off and T_Fmax parameters were significantly shorter in the WSG (Push_Off=0.28 and T_Fmax=0.18) compared to MSG (Push_Off=0.35 and T_Fmax=0.24), while the RG showed a longer Push_Off (0.32) and shorter T_Fmax (0.19). In further analysis, we found that in 14 studied athletes, the explosive strength is in the foreground: 4 in the MSG and WSG and 6 in the RG. For the studied athletes whose explosive strength was predominant, the statistically significant influence of Push_Off and T_Fmax at MSG and WSG was obtained. These findings also result in a recommendation to carry out a thorough analysis of physical preparation and load and to prepare a correction of the program, which would ensure the directional development of the starting force, and not so much the explosive strength.